Overview of Health Worker Training Effectiveness Using Blended andClassical Methods at Bapelkes East Kalimantan - Nur Asiyah; Ratno Adrianto; Irfansyah Baharuddin Pakki (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Health worker training is a strategic effort to improve the competence, professionalism, and readiness of health workers in facing health service challenges. Research. Objective : This study aims to evaluate the application of training methods, participant distribution, and the effectiveness of both methods in improving the competence of health workers, as well as identifying gaps (GAP) in the implementation of training. Research Methods/ Implementation Methods : The research approach is descriptive and evaluative. Data were collected from 2247 trainees based on district/city, gender, employment status, profession, and training method. Results : Large cities such as Samarinda, Balikpapan, and Kutai Kartanegara dominated the number of participants, while remote districts were fewer. The majority of participants were women (77.9%) and ASN (69.5%). The dominant professions are nurses (29.6%) and midwives (24.3%), while minority professions (psychiatrists, medical records, nurse anaesthetists) are very few (<1%). The Classical Method is still dominant (90.5%) with 80% interactive, while the new Blended Learning is 9.48% with 20% interactive. Conclusion/Lesson Learned : Training at UPTD Bapelkes in East Kalimantan Province has reached various professions and districts, but there are still gaps in the distribution of participants, training methods, and participation of minority professions.